Ceftobiprole: First Reported Experience in Osteomyelitis - A MacDonald; G Dow (Canadian Journal of Infectious Diseases and Medical Microbiology)
A 74-year-old man with long-standing diabetes presented with advanced infection of the right forefoot associated with septic arthritis and osteomyelitis involving the second and third metatarsophalangeal joints. Polymicrobial infection, which included methicillin-resistant Staphylococcus aureus, was documented. First-line antibiotic therapy, which included vancomycin, was not tolerated. A durable cure was obtained following a six-week course of intravenous ceftobiprole medocaril combined with local surgery. The present report is the first to administer intravenous ceftobiprole medocaril to a patient with methicillin-resistant S aureus-associated septic arthritis and osteomyelitis.